2024
DOI: 10.3389/fmolb.2023.1330400
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis and delivery of extracellular vesicles: harnessing the power of EVs for diagnostics and therapeutics

Jivin Yu,
Saba Sane,
Ji-Eun Kim
et al.

Abstract: Extracellular vesicles (EVs) are membrane-enclosed particles secreted by a variety of cell types. These vesicles encapsulate a diverse range of molecules, including proteins, nucleic acids, lipids, metabolites, and even organelles derived from their parental cells. While EVs have emerged as crucial mediators of intercellular communication, they also hold immense potential as both biomarkers and therapeutic agents for numerous diseases. A thorough understanding of EV biogenesis is crucial for the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 100 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…The assay is performed using exosomes engineered to vectorize a transcription factor which enables the expression of a reporter gene upon its intracellular delivery [ 88 ]. Thanks to this demonstration, the ability of exosomes to deliver their protein content has been assessed and is regularly reviewed [ 89 ]. Similarly, it has been shown that small RNAs and miRNAs carried by exosomes can be transferred into recipient cells.…”
Section: Exosomes Are Small Specialized Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…The assay is performed using exosomes engineered to vectorize a transcription factor which enables the expression of a reporter gene upon its intracellular delivery [ 88 ]. Thanks to this demonstration, the ability of exosomes to deliver their protein content has been assessed and is regularly reviewed [ 89 ]. Similarly, it has been shown that small RNAs and miRNAs carried by exosomes can be transferred into recipient cells.…”
Section: Exosomes Are Small Specialized Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…In conclusion, understanding the mechanisms underlying EVmediated communication is crucial for harnessing their full potential in therapeutic interventions and diagnostic applications across various health conditions. 10,11 The various importance of EVs in intercellular communication are mentioned in Figure 1.…”
Section: Importance Of Evs In Intercellular Communicationmentioning
confidence: 99%
“…Exosomes play essential roles in various physiological processes, including immune regulation, tissue homeostasis, and neuronal communication. 26,27 In the context of disease, exosomes derived from cancer cells contribute to tumor progression and metastasis by facilitating communication within the tumor microenvironment and influencing recipient cells in distant organs. Conversely, exosomes derived from stem cells exhibit regenerative properties and can promote tissue repair and regeneration.…”
Section: Exosomesmentioning
confidence: 99%
See 1 more Smart Citation